RUSSIA - CHINA STRATEGIC PARTNERSHIP IN THE INDO-PACIFIC REGION: SYNERGIZING GREATER EURASIA WITH BELT AND ROAD INITIATIVE, 2016-2018 - Hendra Manurung (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2019)
Since 2017 to 2018, the world has been living through a period of progressive erosion, or collapse, of international orders have inherited from the Cold-War. Through the election of Donald Trump in 2016 and the rapid increase of U.S aggressive containment policy of Russia and China, which is both a consequence of the gradual erosion which represents deep internal and international contradictions as this process, entered its critical point. Therefore, in responding to the dynamic changes in International Relations, Kremlin has proactively proposed the Greater Eurasian Partnership for the international cooperation agenda in order to adopt within Belt and Road Initiative. This research attempts to assess the linking possibility of the Greater Eurasia integrate with the Belt and Road Initiative for improving cooperation in explanatory research that can be one of the major indicator to implement Vladimir Putin and Xi Jinping agenda-setting in the Indo-Pacific region. The strategic partnership between the development strategies of Russia and China in bilateral, regional, and global relations lays the foundation of improvement cooperation between a number of countries, regions, and organizations. Thus, for the Eurasian Partnership to succeed in the context of Indo-Pacific development, it must strictly comply to World Trade Organization (WTO) rules and take a tolerant attitude toward the diverse mechanisms for cooperation that various countries and regions have developed through. Keywords: Russia, China, Greater Eurasia, Belt and Road Initiative, Indo-Pacific Region Abstrak Sejak 2017 hingga 2018, dunia telah mengalami masa erosi progresif, atau runtuhnya tatanan internasional yang diwarisi dari Perang Dingin. Melalui pemilihan Donald Trump pada tahun 2016 dan peningkatan pesat kebijakan penangkalan agresif Amerika Serikat atas Rusia dan Tiongkok, yang keduanya merupakan konsekuensi dari erosi bertahap yang mewakili kontradiksi internal dan internasional yang mendalam ketika proses ini, memasuki titik kritisnya. Oleh karena itu, dalam menanggapi perubahan dinamis dalam Hubungan Internasional, Kremlin telah secara proaktif mengusulkan Kemitraan Eurasia Besar untuk agenda kerja sama internasional agar dapat diadopsi dalam Belt and Road Initiative. Penelitian ini mencoba untuk menilai kemungkinan keterkaitan Eurasia Besar dengan Inisiatif Sabuk dan Jalan untuk meningkatkan kerja sama dalam penelitian penjelas yang dapat menjadi salah satu indikator utama untuk mengimplementasikan Vladimir Putin dan penetapan agenda Xi Jinping di kawasan Indo-Pasifik. Kemitraan strategis antara strategi pembangunan Rusia dan Cina dalam hubungan bilateral, regional, dan global meletakkan fondasi peningkatan kerjasama antara sejumlah negara, wilayah, dan organisasi. Dengan demikian, agar Kemitraan Eurasia berhasil dalam konteks pembangunan Indo-Pasifik, ia harus benar-benar mematuhi aturan Organisasi Perdagangan Dunia (WTO) dan mengambil sikap toleran terhadap beragam mekanisme kerja sama yang telah dikembangkan oleh berbagai negara dan wilayah. Kata-kata kunci: Rusia, Tiongkok, Terbesar Eurasia, Inisiatif Sabuk dan Jalan, kawasan Indo-Pasifik